Socialization of The Application of Dynamic Regression Analysis Models in Determining Factors Affecting the Economic Growthof Small and Medium Enterprises (SMES) In padangsidimpuan City Using the Ordinary Least Square (OLS) Method - Lilis Saryani; Ahmad Sayuti Pulung; Abdelina (Yayasan Perguruan Kampus, 2024)
Micro, Small and Medium Enterprises (MSMEs) are a very important economic sector in Indonesia, and also in Padangsidimpuan City. According to data from the Ministry of Cooperatives and Small and Medium Enterprises, in 2020, the number of MSMEs in Indonesia reached 64.2 million business units, with a contribution to Gross Domestic Product (GDP) of 60.34% and creating employment of 97.18 million people. However, despite its great potential, the MSME sector still faces various obstacles in developing its business, especially in increasing economic growth. One of these obstacles is the limited resources owned by MSMEs, both in terms of capital, labor, market access, technology, and so on. Padangsidimpuan City as one of the cities in North Sumatra Province has great potential in the development of MSMEs. One of the analytical methods that can be used to analyze the factors that influence the economic growth of MSMEs is the dynamic regression analysis model using the Ordinary Least Square (OLS) method. The urgency of the research is the increasing role of MSMEs as contributors to the economic growth of Indonesia and Padangsidimpuan City in particular. MSMEs are considered a strategic sector in economic development, especially in creating jobs and increasing the competitiveness of the national economy. However, MSMEs still experience obstacles in developing their businesses, especially in increasing economic growth. The purpose of this study is to analyze the factors that influence the economic growth of MSMEs in Padangsidimpuan City using the dynamic regression analysis model and the Ordinary Least Square (OLS) method. In addition, this study also aims to provide recommendations to the government and business actors in increasing the economic growth of MSMEs in Padangsidimpuan City.